Pengaruh Pertumbuhan Ekonomi, Pendapatan Asli Daerah, Dana Alokasi Umum, Dana Alokasi Khusus terhadap Indeks Pembangunan Manusia dengan Belanja Pendidikan dan Kesehatan sebagai Variabel Intervening (Studi Empiris pada Kabupaten/Kota di Jawa) - Hayati, Anisa Nur, Drs. Atwal Arifin, Ak.,M.Si (2015)
This study aims to prove empirically that Economic Growth (PE), the General Allocation Fund (DAU), the Special Allocation Fund (DAK), Local Revenue (PAD), affect Human Development Index with the Allocation of expenditure on education (BPDDK) and expenditure on health (BKSHT) as intervening variable. The population in this study is 119 regencies/cities in Java during 2009-2012, with the total samples of 62 regencies/cities. The sampling method used in this study is purposive sampling. The result of sobel test showed that PAD and DAU significant effect on IPM through BPDDK. Whereas PE and DAK no significant effect on IPM through BPDDK. Based on path analisys showed that to determine the effect of PE, DAU and DAK on IPM selected indirect path through BPDDK, whereas PAD selected direct path without going through BPDDK. Further, PE and DAU significant effect on IPM through BKSHT. Whereas PAD and DAK no significant effect on IPM through BKSHT. Based on path analisys showed that to determine the effect of PE, DAU and DAK on IPM selected indirect path through BKSHT, whereas PAD on IPM selected direct path without going through BKSHT.